Lesão renal aguda e escolha de métodos dialíticos - Pires, Romulo Geraldo Barbosa [UNIFESP] (2016)
Objective: To evaluate the factors that led the nephrologist to choose the initial method of renal replacement therapy between methods: intermittent, extended daily dialysis or continuous renal replacement therapy for patients hospitalized with acute kidney injury or chronic kidney disease worsened requiring dialysis and compare the clinical outcome of patients undergoing different methods. Methods: Prospective observational cohort study, with nine mouths of nephology team follow up in a tertiary hospital and included 182 patients with acute kidney injury or chronic kidney disease worsened, dialyzed in that period. Data collection was initiated at the start of renal replacement therapy until clinical outcome, it could be kidney recovery, chronic dialysis, death or decision for palliative care. Results: 69 patients hemodynamically stable received intermittent method; 19 hemodynamically unstable patients with vasoactive drug above 0.5 micrograms per kilogram per minute received the continuous method; 94 patients received extended hemodialysis because of hemodynamic instability with vasoactive drugs to 0.5 micrograms per kilogram per minute. Among those 94 cases there were 9 patients who had medical indication receiving the continuous method, but received the extended method due to technical availability for the continuous method. The improvement of renal function and chronic dialysis were higher among patients who received intermittent method while the probability of death was higher among patients who received continuous and extended methods. Conclusions: The choice of the dialysis method depends on predominantly hemodynamic factors of patients and, despite some factors other than that were strongly related to the continuous method, such as sepsis and heart failure, these other factors are also closely related to hemodynamics alterations. The extended TSR method is a great option for the treatment of hemodynamically unstable patients and is often used as a substitute for continuous method. However, it is not a full substitute because when there was replacement, occurs a significant suspension of the dialysis sessions before the end due to hypotension. Other factors such as liver failure, increased intracranial pressure and the risk of bleeding should really be taken into consideration when choosing the method, but did not appear in our study. The chronicity of outcomes or improvement of renal function demonstrated an increase compared to the prior condition of kidney patients than the previously chosen methods. Mortality was similar in extended and continuous methods and much lower in the intermittent method, a fact attributable to minor gravity in this group.